Iron Speciation in Beans (Phaseolus vulgaris) Biofortified by Common Breeding. Issue 9 (14th August 2014) - Hoppler, Matthias; Egli, Ines; Petry, Nicolai; Gille, Doreen; Zeder, Christophe; Walczyk, Thomas; Blair, Matthew W.; Hurrell, Richard F.
Abstract The iron storage protein ferritin is a potential vehicle to enhance the iron content of biofortified crops. With the aim of evaluating the potential of ferritin iron in plant breeding, we used species‐specific isotope dilution mass spectrometry to quantify ferritin iron in bean varieties with a wide range of total iron content. Zinc, phytic acid, and polyphenols were also measured. Total iron concentration in 21 bean varieties ranged from 32 to 115 ppm and was positively correlated with concentrations of zinc (P = 0.001) and nonferritin bound iron (P < 0.001). Ferritin iron ranged from 13% to 35% of total iron and increased only slightly in high iron beans (P = 0.007). Concentrations of nonferritin bound iron and phytic acid were correlated (P = 0.001), although phytic acid:iron molar ratio decreased with increasing iron concentration (P = 0.003). Most iron in high iron beans was present as nonferritin bound iron, which confirms our earlier finding showing that ferritin iron in beans was lower than previously published. As the range of ferritin iron content in beans is relatively narrow, there is less opportunity for breeders to breed for high ferritin. The relevance of these findings to the extent of iron absorption depends on resolving the question of whether ferritin iron is absorbed or not to a greater extent than nonferritin bound iron.